1986
DOI: 10.3109/17453678609157924
|View full text |Cite
|
Sign up to set email alerts
|

Micromotion in knee arthroplasty

Abstract: 1.The coordinate system for unicompartmental and total prostheses. 2. The Venn diagram used in the Lund assessment system. 3. Total Condylar knee prosthesis. 17 4. Modular (Marmor) knee prosthesis. 5. Kinematic Migration:original position to a new resting position. Inducible displacement:the prosthesis is detachable from its resting position. Rigid body:Rigid-body model (RBM): A configuration of three or more non-collinear markers representing the bodies of interest (prostheses or bone segments), and used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 118 publications
(140 reference statements)
1
11
0
Order By: Relevance
“…The limits of the 95% tolerance interval for precision did not exceed 0.09 mm and 0.14°. These values are within the reported range for RSA techniques (<0.1 to 0.7 mm for translations and 0.03° to 0.5° for rotations (Ryd 1986 , Snorrason and Kärrholm 1990 , Önsten et al 1995 , Kärrholm et al 1997 , Østgaard et al 1997 , Önsten et al 2001 )). Yet, CTSA does not rely on bone/implant markers and offers the user-friendliness of EBRA but with more accuracy.…”
Section: Discussionsupporting
confidence: 82%
“…The limits of the 95% tolerance interval for precision did not exceed 0.09 mm and 0.14°. These values are within the reported range for RSA techniques (<0.1 to 0.7 mm for translations and 0.03° to 0.5° for rotations (Ryd 1986 , Snorrason and Kärrholm 1990 , Önsten et al 1995 , Kärrholm et al 1997 , Østgaard et al 1997 , Önsten et al 2001 )). Yet, CTSA does not rely on bone/implant markers and offers the user-friendliness of EBRA but with more accuracy.…”
Section: Discussionsupporting
confidence: 82%
“…Our radiographic results show a small remaining varus position of the tibial component and for the arthroplasty. This is not uncommon in other series [17,18]. Our patients had frequently the most advanced stages of the OA disease, which makes surgery more demanding.…”
Section: Discussionmentioning
confidence: 93%
“…The other longitudinal study found that biomarker levels, specifically osteocalcin and cross-linked carboxyterminal telopeptide of type I collagen (ICTP), were elevated before implant migration as assessed by radiosteriometric analsysis (RSA) 18 . Early implant migration is considered a risk factor for late loosening 55 and, therefore, the authors concluded that early elevation in these biomarkers is predictive of future migration. In our study, patients were categorized based on routine radiographic analysis and therefore, biomarker levels in the current study relate directly to the clinical manifestation of osteolysis.…”
Section: Discussionmentioning
confidence: 99%